The ecological nature of whole river macrosystems: new perspectives from the riverine ecosystem synthesis - Thorp, James H.; Thoms, Martin C.; Delong, Michael D.; Maasri, Alain (Frontiers in Ecology and Evolution, 2023)
Opportunities to understand and protect natural aquatic diversity in both relatively pristine and managed rivers can be enhanced with a comprehensive, system-wide understanding of a river’s hydrogeomorpholgy and its effects on ecological structure and functioning from the river’s headwaters to its terminus in an ocean, lake, or natural endorheic basin. While a moderate number of macrosystem ecology studies have been undertaken recently in headwaters, comparable ecological approaches to studying whole rivers or at least their larger components from upstream to downstream are relatively rare. This is partially correlated with the paucity of applicable river ecosystem models developed over the last half century which could otherwise provide diverse, testable tenets (hypotheses). This manuscript focuses on a 15+ year updated, system-wide analysis of the applicability of the 17 tenets included in our previously published, lotic model - the Riverine Ecosystem Synthesis, or RES. We also propose here four new tenets and analyze the system-wide applicability of the revised RES. Those new tenets hypothesize that: (H-18) “The range and degree of impacts of a Functional Process Zone on biodiversity and ecological processes differ among several factors, including types of FPZs, total river area covered, and dependent variables examined, even in the same river network position”; (H-19) “The degree of ecological differences among types of FPZs vary seasonally with the process being examined while also differing among types of life history characteristics - especially when contrasting responses among seasonal periods of either maximum or minimum growth and reproduction”; (H-20) “The relative importance of in-stream versus watershed drivers of ecological processes in streams can vary within macrosystems and among ecoregions and partially depends on elevation, terrestrial characteristics (natural or human modified), and FPZ type and extent”; and (H-21) “The provision of ecosystem services varies significantly with FPZ type, river size, and location vis-à-vis human populations”. Where appropriate, we also evaluate aspects of several other models published by colleagues that pertain to river ecology.